TiN / SiO2 nano-laminate ultralow reflectance film and preparation method thereof

CN122979858APending Publication Date: 2026-10-27EAST CHINA UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611487577.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-23
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

为降低反射损耗,现有技术尝试采用多层减反射结构、金属-氧化物复合薄膜、以及石墨烯复合透明导电薄膜等方案,并通过多界面干涉效应实现减反射功能,但均难以实现突破常规物理极限的超低反射效果

Benefits of technology

(1)可见光区超低反射性能:通过精确光学设计,本方案制备的TiN/SiO2多层膜结构在400-700nm波段的平均反射率可低至0.2%以下,远低于单层TiN膜(通常高于15%)和ITO透明导电薄膜(约4%-10%)。近乎零反射的特性能够最大限度地提升光能利用效率,应用于光伏器件时可显著增加短路电流密度,应用于显示器件时可有效提高显示对比度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122979858A_ABST
    Figure CN122979858A_ABST
Patent Text Reader

Abstract

The application discloses a TiN / SiO2 nano-laminated ultra-low reflection film and a preparation method thereof, and belongs to the technical field of optical film preparation. The method comprises the following steps: extracting optical constants of TiN and SiO2, and establishing a multilayer film structure model; taking minimization of average reflectivity in a 400-700 nm wave band as an objective, taking a peak reflectivity lower than 0.5% as a constraint, defining the peak reflectivity, and performing reverse optimization with a weighted penalty function as an optimization objective; adopting PE-ALD technology to deposit and obtain a multilayer film structure; performing reverse fitting correction after actual measurement of a spectrum, and repeatedly preparing until the actual measurement average reflectivity is lower than 0.2% and the peak reflectivity is lower than 0.5%. The prepared product has an average reflectivity lower than 0.2% in the 400-700 nm wave band, which is superior to traditional transparent conductive materials such as ITO; and the combination of optical simulation global optimization and ALD sub-nanometer level deposition precision avoids the inefficiency and uncertainty of the traditional trial-and-error method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of optical thin film preparation technology, and in particular to a TiN / SiO2 nanolayered ultra-low reflection film and its preparation method. Background Technology

[0002] Transparent conductive films are core electrode materials for optoelectronic devices such as flexible displays, touch screens, and thin-film photovoltaics. Currently, the mainstream material is indium tin oxide (ITO), which still exhibits approximately 4-10% surface reflection loss in the visible light region. To reduce reflection loss, existing technologies have attempted to employ multilayer antireflection structures, metal-oxide composite films, and graphene composite transparent conductive films, achieving antireflection through multi-interface interference effects. However, none of these methods can achieve ultra-low reflection effects that break through conventional physical limits.

[0003] The reason for this is that the higher the free carrier concentration and the better the conductivity of transparent conductive materials, the higher their refractive index and extinction coefficient will be, which will inevitably lead to an increase in surface reflectivity. "The better the conductivity, the higher the reflectivity" is the inherent contradiction of this type of material, which cannot be solved by a single material. At the same time, the traditional λ / 4 antireflection scheme is only optimized for a single wavelength. After deviating from the center wavelength, the reflectivity will rise rapidly, and it is impossible to achieve ultra-low reflectivity over a wide spectrum (400-700nm). In addition, the trial-and-error method has limited search dimensions, making it difficult to locate the globally optimal thickness combination in multilayer film systems.

[0004] Therefore, there is an urgent need to develop a preparation method that can start from ultra-low reflectivity targets, systematically derive the optimal nanolayer structure through reverse design, and combine it with high-precision atomic layer deposition technology to achieve "design-as-you-go" preparation. Summary of the Invention

[0005] The purpose of this invention is to provide a TiN / SiO2 nanolayered ultra-low reflectance film and its preparation method. The aim is to systematically derive the optimal nanolayered structure based on the target optical performance by combining a reverse design strategy with atomic layer deposition technology, so as to solve the above-mentioned problems.

[0006] To achieve the above objectives, this invention provides a method for preparing a TiN / SiO2 nanolayered ultra-low reflectance film, comprising the following steps: Step S1: Plasma-enhanced atomic layer deposition (PE-ALD) is used to deposit monolayer TiN and monolayer SiO2 films on a reference substrate. The optical constants of TiN and SiO2 in the visible to near-infrared bands are extracted by measuring with a spectroscopic ellipsometry and fitting with a dispersion model. The data are then imported into the material library of the optical thin film design software. Step S2: Create an air / (TiN / SiO2) structure in the optical thin film design software. n / A multilayer film structure model for a transparent substrate, wherein the thickness of a single TiN film is not less than 2nm and the thickness of a single SiO2 film is not less than 10nm; Step S3: Perform inverse global optimization on the multilayer film structure model, assuming discrete sampling points in the 400-800nm ​​visible light wavelength range are... ( i =1,2,…,m), the multilayer film structure model includes the number of periods n and the thicknesses of each TiN sublayer and SiO2 sublayer as adjustable design variables. The theoretical reflectance at each sampling point is ;in The calculations, based on the transfer matrix method and performed by optical thin film design software, specifically involve multilayer film structures at wavelengths... Input admittance at the location It is obtained recursively from the characteristic matrix of the membrane system; Define average reflectance: ; in: — Number of wavelength sampling points; — The reflectivity at the i-th sampling wavelength is calculated by Macleod based on the transfer matrix method; —The complex refractive index of the incident medium, where the incident medium is air, take = 1.0 + 0i; — Multilayer film structures at wavelength The input admittance at the point is obtained recursively from the characteristic matrix of the membrane system.

[0007] The peak reflectivity constraint is set as follows: ; Define the overall objective function as a weighted penalty function for the constraints of average reflectance and peak reflectance: in =100 is the penalty factor. When the peak reflectivity exceeds the 0.5% threshold, a large penalty term is applied to ensure that the optimization prioritizes meeting the peak constraint. By making the weighted penalty function Minimize the thickness to obtain the design thickness of each sublayer; Step S4: Based on the designed thickness of each sublayer output in Step S3, TiN thin films and SiO2 thin films are alternately deposited from bottom to top on the target transparent substrate using plasma-enhanced atomic layer deposition technology to form a (TiN / SiO2) layer with SiO2 layer as the top layer. n Nanostructured stacked structure; Step S5: Measure the absolute reflectance spectrum of the sample obtained in step S4 in the 400-700nm wavelength range; Step S6: Perform reverse fitting between the measured absolute reflectance spectrum and the theoretical simulation spectrum in step S3, and correct the thickness of each sublayer or recalibrate the optical constants of the material based on the fitting deviation; Step S7: Repeat steps S4 to S6 until the measured average reflectance is less than 0.2% and the peak reflectance is less than 0.5%, thus obtaining the TiN / SiO2 nanolayered ultra-low reflectance film.

[0008] Preferably, in step S1: when depositing the TiN thin film, TiCl4 is used as the titanium precursor and NH3 plasma is used as the nitrogen source, and the deposition temperature is 80℃-120℃; when depositing the SiO2 thin film, bis(diethylamino)silane is used as the silicon precursor and O2 plasma is used as the oxygen source, and the deposition temperature is 80℃-120℃. The ellipsometric spectrum of the TiN thin film was fitted using the Tauc-Lorentz oscillator model, and the ellipsometric spectrum of the SiO2 thin film was fitted using the Cauchy dispersion model. The refractive index and extinction coefficient at each wavelength were obtained by inversion.

[0009] Preferably, the (TiN / SiO2) in step S2 n In this context, n ranges from 1 to 6.

[0010] Preferably, n takes the value of 3-5.

[0011] Preferably, in step S3, the reverse global optimization iterates through the layers one by one with n as a discrete variable. At each value of n, the initial thickness of each TiN sublayer is set to 10 nm, and the initial thickness of each SiO2 sublayer is set to 30 nm, to globally optimize the thickness of each sublayer, thus making the weighted penalty function... minimize.

[0012] Preferably, before step S4, a substrate pretreatment step is included: the target transparent substrate is sequentially ultrasonically cleaned in acetone, isopropanol, and deionized water, dried with high-purity nitrogen, and then placed in a plasma-enhanced atomic layer deposition reaction chamber, where a vacuum is drawn until the background vacuum level is below 3 × 10⁻⁶. -2 Torr, then heat the substrate to 100°C and hold it at that temperature until thermal equilibrium is reached.

[0013] Preferably, in step S5, an ultraviolet-visible-near-infrared spectrophotometer is used to measure the measured absolute reflectance spectrum under near-normal incidence conditions.

[0014] Preferably, the constraints for the backfit in step S6 are: the optical constants of TiN are adjusted within ±5% of the calibration value, the refractive index of SiO2 is adjusted within ±1% of the calibration value and the extinction coefficient is fixed at zero, and the thickness of each sublayer is adjusted within ±15% of the design value; when the fitting objective function decreases by less than one part per million for five consecutive iterations, or the goodness of fit R... 2 The fitting process stops when the value is greater than 0.999 or when the upper limit of 10,000 iterations is reached.

[0015] Preferably, the specific method for correcting the thickness of each sublayer or recalibrating the optical constants of the material in step S6 is as follows: when the measured average reflectivity is between 0.2% and 0.3% and the measured peak reflectivity is between 0.5% and 0.7%, the atomic layer deposition cycle number is adjusted proportionally to the ratio of the fitted actual thickness to the designed thickness; when the measured average reflectivity is ≥0.3% or the optical constants of the material deviate from the calibration value by more than 5%, the optical constants of the material are recalibrated and steps S2 to S3 are re-executed to optimize the structural design; if the standard is still not met after three consecutive rounds of correction, the equipment is checked.

[0016] The present invention also provides a TiN / SiO2 nanolayered ultra-low reflectance film prepared by the above preparation method.

[0017] Preferably, in the 400-700nm visible light band, the average reflectivity of the TiN / SiO2 nanolayer ultra-low reflectivity film is less than 0.2%, and the peak reflectivity is less than 0.5%.

[0018] The TiN / SiO2 nanolayered ultra-low reflection film prepared by this invention has both excellent conductivity and ultra-low reflection characteristics in the visible light region. It can be used as an ultra-low reflection transparent electrode in photovoltaic devices, flexible display devices and smart window devices, and can also be used in other optoelectronic device fields that require both transparent conductivity and ultra-low reflection functions.

[0019] Therefore, the present invention has the following beneficial effects: (1) Ultra-low reflectivity in the visible light region: Through precise optical design, the TiN / SiO2 multilayer film structure prepared by this method can achieve an average reflectivity of less than 0.2% in the 400-700nm wavelength band, which is much lower than that of a single-layer TiN film (usually higher than 15%) and ITO transparent conductive film (about 4%-10%). The near-zero reflectivity can maximize the light energy utilization efficiency. When applied to photovoltaic devices, it can significantly increase the short-circuit current density, and when applied to display devices, it can effectively improve the display contrast.

[0020] (2) Wideband anti-reflection effect: Through the multi-interface interference effect of the multilayer film structure, the anti-reflection effect is not limited to a single wavelength, but achieves a flat ultra-low reflection response in the entire visible light region, thereby ensuring that the device presents an optical appearance without color deviation under natural light.

[0021] (3) Design-as-you-go precision: By combining the global optimization capabilities of optical simulation software with the sub-nanometer deposition precision of atomic layer deposition technology, a strong correlation between theoretical design, experimental preparation, and performance verification is achieved, fundamentally avoiding the problems of low development efficiency and poor repeatability of the traditional "trial and error method". The overall method has a closed-loop optimization process, which further ensures the stability and repeatability of product performance.

[0022] The technical solution of the present invention will be further described in detail below with reference to embodiments and accompanying drawings. Attached Figure Description

[0023] Figure 1 This is a schematic diagram of the optimal structure obtained in Example 1; Figure 2 The measured reflectance of the TiN / SiO2 nanolayered ultra-low reflectance film prepared in Example 1; Figure 3 The measured reflectance of the TiN / SiO2 nanolayered ultra-low reflectance film prepared in Example 2; Figure 4 The measured reflectance of the TiN / SiO2 nanolayered ultra-low reflectance film prepared in Example 3; Figure 5 The measured reflectance of the TiN / SiO2 nanolayered ultra-low reflectance film prepared in Comparative Example 1 is shown. Figure 6 The measured reflectance of the TiN / SiO2 nanolayered ultra-low reflectance film prepared in Comparative Example 2 is shown. Detailed Implementation

[0024] The technical solution of the present invention will be further described below with reference to the accompanying drawings and embodiments.

[0025] Unless otherwise defined, the technical or scientific terms used in this invention shall have the ordinary meaning as understood by one of ordinary skill in the art to which this invention pertains.

[0026] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can be appropriately combined to form other embodiments that can be understood by those skilled in the art. These other embodiments are also covered within the scope of protection of this invention.

[0027] Unless otherwise specified, the reagents, instruments, and equipment used in this invention are all commonly used by those skilled in the art.

[0028] Example 1 This embodiment provides a TiN / SiO2 nanolayered ultra-low reflectance film and its preparation method, specifically including the following steps: Step S1: On a glass substrate, a single-layer TiN film and a single-layer SiO2 film are deposited respectively using plasma-enhanced atomic layer deposition technology as reference samples for subsequent optical simulation.

[0029] TiN thin film deposition parameters: TiCl4 as the titanium precursor, source bottle temperature 50℃, Ar flow rate 300 sccm; NH3 plasma as the nitrogen source, ICP power 2800 W; deposition temperature 100℃; ALD cycling parameters: TiCl4 pulse time 1s → Ar purge 7s → NH3 plasma ignition time 5s → Ar purge 10s. Ellipsometry calibration showed that the growth rate of TiN at 100℃ was approximately 0.02 Å / cycle.

[0030] In this embodiment, the thickness of the TiN monolayer film is 30 nm, corresponding to approximately 1500 ALD cycles.

[0031] SiO2 thin film deposition parameters: silicon precursor was BDEAS (bis(diethylamino)silane), source bottle temperature 73℃; oxygen source was O2 plasma, ICP power 700W; deposition temperature 100℃; ALD cycle parameters were: BDEAS pulse time 2.2s → N2 purge 3s → O2 plasma ignition time 3.5s → N2 purge 5s. Ellipsometry calibration showed that the SiO2 growth rate at 100℃ was approximately 0.144 Å / cycle. In this embodiment, the SiO2 monolayer thickness was 30nm, corresponding to approximately 208 ALD cycles.

[0032] Optical constant measurement and import: Epylvariance spectra of TiN and SiO2 monolayer films deposited on silicon reference wafers were measured using a JAWoollam M-2000 spectrometer in the visible-near-infrared band (300-1700 nm) with varying angles (60°, 70°). The ellipsometric spectrum of the TiN film was fitted using the Tauc-Lorentz oscillator model, and the Ψ and Δ spectra of the SiO2 film were fitted using the Cauchy dispersion model. The refractive index and extinction coefficient at each wavelength were then obtained through inversion. Among them: —Refractive index (real part), characterizing a material's ability to modulate the phase of light; —Extinction coefficient (imaginary part), characterizing the light absorption loss of a material; The fitted result - The data was imported into the material library of Essential Macleod software in ASCII tabular format (wavelength λ in nm, n and k are dimensionless values) as the base database for subsequent optical simulations of nanolayered structures.

[0033] Step S2: Create an air / (TiN / SiO2) structure in Essential Macleod software. n The multilayer film structure model of the glass substrate adopts a bottom-up growth sequence. First, a TiN layer is deposited on the substrate (in contact with the substrate interface to ensure that the conductive layer is close to the substrate). Then, a SiO2 layer is deposited on the TiN layer (as a low refractive index medium layer to control the optical interference effect). The above TiN / SiO2 pair is repeated until n cycles are completed. The top layer is SiO2 (which plays an additional role in anti-reflection surface passivation).

[0034] The stack adopts a bottom-up growth sequence, that is, it is deposited layer by layer starting from the substrate surface: first, a TiN layer is deposited on the substrate (in contact with the electrode / substrate interface to ensure that the conductive layer is close to the substrate, which is conducive to the charge collection of the device); then, a SiO2 layer is deposited on the TiN layer (as a low refractive index dielectric layer to control the optical interference effect); the above (TiN / SiO2) pair is repeated until n cycles are completed; the top layer is SiO2 (that is, the top layer is a low refractive index layer, which plays an additional anti-reflection surface passivation role).

[0035] The number of cycles n is set to 1-6; the initial optimization starts from n=3; during the simulation, n is used as a discrete variable for scanning optimization, and the thickness of each sublayer is globally optimized for each value of n.

[0036] TiN monolayer thickness: lower limit 2 nm: to ensure electrical continuity of the TiN layer in the thickness direction (avoiding conduction interruption caused by tunneling effect); SiO2 monolayer thickness lower limit 10 nm: to ensure complete coverage of the SiO2 layer deposited by ALD and sufficient refractive index modulation capability; the thickness should be as thin as possible while ensuring optimal performance.

[0037] Model input operation: The TiN and SiO2 extracted in step S1 - Data in ASCII format ( λ List, n List, kImport the materials from the Macleod Materials Database and name them “TiN_TALD” and “SiO2_TALD” respectively. In the Stack Designer module, define the following in sequence: substrate (Glass, whose n(λ)-k(λ) is provided by the Macleod built-in library or imported through ellipsometer measurement) → alternately add TiN_TALD and SiO2_TALD layers → set the number of periods to n → define the top layer as SiO2. Initially, set the thickness of each TiN sublayer to 10 nm and the thickness of each SiO2 sublayer to 30 nm as the starting point for the optimization algorithm.

[0038] Step S3: Let the discrete sampling points in the wavelength range of 400-800nm ​​be... ( i =1,2,…,m), the multilayer film structure model includes the number of periods n and the thicknesses of each TiN sublayer and SiO2 sublayer as adjustable design variables. The theoretical reflectance at each sampling point is .in Calculated by EssentialMacleod based on the transfer matrix method, specifically by the multilayer film structure at wavelength λ i Input admittance at the location It is obtained by recursion through the characteristic matrix of the membrane system.

[0039] Define average reflectance: Define average reflectance: ; in: — Number of wavelength sampling points; — The reflectivity at the i-th sampling wavelength is calculated by Macleod based on the transfer matrix method; —The complex refractive index of the incident medium, where the incident medium is air, take = 1.0 + 0i; — Multilayer film structures at wavelength The input admittance at the point is obtained recursively from the characteristic matrix of the membrane system.

[0040] Define peak reflectance: ; Set the peak reflectivity constraint as follows <0.5%.

[0041] Define the overall objective function as a weighted penalty function for the constraints of average reflectance and peak reflectance: Where α=100 is the penalty factor. When the peak reflectivity exceeds the 0.5% threshold, a large penalty term is applied to ensure that the optimization prioritizes meeting the peak constraint.

[0042] Using n as a discrete variable, iterate through the layers one by one. For each value of n, starting from an initial thickness of 10 nm for each TiN sublayer and 30 nm for each SiO2 sublayer, perform global optimization on the thickness of each sublayer to optimize the weighted penalty function. Minimize to obtain the design thickness of each sublayer.

[0043] Step S4: Place the glass substrate in acetone, isopropanol and deionized water in sequence for ultrasonic cleaning for 15 minutes each. The ultrasonic frequency is 40kHz, the power is 200W and the temperature is 25±2℃. After each cleaning step, dry it with high-purity nitrogen gas (purity 99.999%) and send it to the sample stage of the plasma-enhanced atomic layer deposition reaction chamber.

[0044] Close the chamber door, and start the mechanical pump and molecular pump assembly to evacuate the reaction chamber until the background vacuum level is below 3 × 10⁻⁶. - 2 Torr, start the heating system to heat up to 100°C at 5°C / min and hold for 120 minutes until thermal equilibrium is reached.

[0045] Based on the designed thickness of each sublayer output in step S3, the number of ALD cycles is calculated according to the growth rate, and the ALD program is edited for deposition.

[0046] The optimal structure obtained in this embodiment is n=3 (six layers), as shown in the following figure. Figure 1 As shown, the deposition conditions are the same as S1, and the deposition sequence from bottom to top is: TiN (38nm, 1900 cycles) / SiO2 (19nm, 132 cycles) / TiN (65nm, 3250 cycles) / SiO2 (24nm, 167 cycles) / TiN (44nm, 2200 cycles) / SiO2 (79nm, 549 cycles), with SiO2 as the top layer.

[0047] Step S5: Using a UV-Vis-NIR spectrophotometer, measure the absolute reflectance spectrum of the prepared sample in the 400-700 nm wavelength range under near-normal incidence (8° incident angle) conditions. .

[0048] Step S6: Import the measured reflectance spectrum into EssentialMacleod software. Using the constraints of TiN's optical constants within ±5% of the calibrated value, SiO2's refractive index within ±1% of the calibrated value (with the extinction coefficient fixed at zero), and each sublayer thickness within ±15% of the design value, perform inverse fitting to make the theoretical spectrum approximate the measured spectrum. When the rate of decrease of the fitting objective function is less than one part per million for five consecutive iterations, or the goodness of fit R... 2 Fitting stops when the value is greater than 0.999 or when the upper limit of 10,000 iterations is reached. In this embodiment, the goodness of fit R is... 2 The measured spectrum reached above 0.999, and the measured spectrum matched the theoretical simulated spectrum well.

[0049] Step S7, the measured reflectance in step S5 of this embodiment is as follows: Figure 2 As shown in the figure, points 1-4 represent the four corner regions of the sample, and point 5 represents the central region of the sample. The average reflectance is 0.04%, and the measured peak reflectance is less than 0.2%, meeting the target of "average reflectance less than 0.2% and peak reflectance less than 0.5%". Therefore, the sample is qualified and no further iterative correction is needed. The obtained TiN / SiO2 nanolayered ultra-low reflectance film has an average reflectance of 0.04% and a peak reflectance of less than 0.2% in the 400-700nm visible light band.

[0050] Example 2 The difference between this embodiment and Embodiment 1 is that in step S3, the optimization design is performed with only the average reflectance constrained, without applying a peak reflectance constraint; and the designed thickness of each sublayer is different in step S4. The deposition order from bottom to top is: TiN (38 nm, 1900 cycles) / SiO2 (19 nm, 132 cycles) / TiN (70 nm, 3500 cycles) / SiO2 (29 nm, 201 cycles) / TiN (44 nm, 2200 cycles) / SiO2 (79 nm, 549 cycles), with SiO2 as the top layer. After measurement in step S5, the reflectance spectra in the 400-700 nm band were collected at multiple points on the glass sample, as shown below. Figure 3 As shown in the figure, points 1-4 are the four corner areas of the sample, and point 5 is the central area of ​​the sample. The average reflectance is 0.4%, the reflectance in the 650-700 nm band is relatively high, and the peak reflectance exceeds 0.7%.

[0051] Example 3 The difference between this embodiment and Embodiment 1 is that in step S3, the optimization design is performed with only the average reflectance constrained, without applying a peak reflectance constraint; and the designed thickness of each sublayer is different in step S4. The deposition order from bottom to top is: TiN (30 nm, 1500 cycles) / SiO2 (15 nm, 104 cycles) / TiN (95 nm, 4750 cycles) / SiO2 (28 nm, 194 cycles) / TiN (44 nm, 2200 cycles) / SiO2 (85 nm, 590 cycles), with SiO2 as the top layer. After measurement in step S5, the reflectance spectra in the 400-700 nm band were collected at multiple points on the glass sample, as shown below. Figure 4 As shown in the figure, points 1-4 represent the four corner regions of the sample, and point 5 represents the central region of the sample. The average reflectance is 0.45%, and the reflectance in the 450-500 nm band is relatively high.

[0052] Comparative Example 1 On a glass substrate, a TiN layer and a SiO2 layer were sequentially deposited using plasma-enhanced atomic layer deposition (ALD) to form a TiN / SiO2 bilayer structure. The TiN layer was 35 nm thick (corresponding to 1750 ALD cycles), the SiO2 layer was 90 nm thick (corresponding to 625 ALD cycles), and the top layer was SiO2. The reflectance spectrum in the 400-700 nm wavelength range was measured at multiple points on the glass sample, and the results are as follows: Figure 5 As shown in the figure, points 1-4 represent the four corner regions of the sample, and point 5 represents the central region of the sample. The results show that the average reflectance is 1.6%, and the reflectance is relatively high in the 400-500 nm band.

[0053] Comparative Example 2 On a glass substrate, TiN, SiO2, TiN, and SiO2 layers were deposited sequentially from bottom to top using plasma-enhanced atomic layer deposition (ALD), forming a four-layer TiN / SiO2 / TiN / SiO2 stacked structure of equal thickness. Each TiN layer was 10 nm thick (corresponding to 500 ALD cycles), each SiO2 layer was 45 nm thick (corresponding to 313 ALD cycles), and the top layer was SiO2. The reflectance spectra in the 400-700 nm wavelength range were measured at multiple points on the glass sample, and the results are as follows: Figure 6 As shown in the figure, points 1-4 represent the four corner areas of the sample, and point 5 represents the central area of ​​the sample. The average reflectance is 2.68%, which is relatively high overall.

[0054] Therefore, Comparative Examples 1 and 2 are empirically designed structures without inverse optimization, and their reflectance is higher than 1.5%. Although Examples 2 and 3 were inversely optimized using Macleod and are both non-uniform six-layer structures, the optimization only constrained the average reflectance without applying a hard constraint on the peak reflectance, resulting in local reflection peaks (peak values ​​exceeding 0.7%) in the reflection spectrum, which could not meet the requirement of peak values ​​being lower than 0.5%. Only Example 1, which adopted the dual hard constraint strategy described in this invention, constrained both the average and peak reflectance, achieving an average reflectance as low as 0.04% and a peak value lower than 0.2%. This shows that simply "using Macleod software" or "increasing the number of cycles" is insufficient to achieve ultra-low reflectance. The key lies in the constraint conditions of the optimization target. The minimum average reflectance must be the primary objective, and a peak reflectance lower than 0.5% must be used as a hard constraint to obtain an ultra-low reflectance film that meets the requirements.

[0055] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing a TiN / SiO2 nanolayered ultra-low reflectance film, characterized in that, Includes the following steps: Step S1: Plasma-enhanced atomic layer deposition (PEALD) is used to deposit monolayer TiN and monolayer SiO2 films on a reference substrate. Optical constant data of TiN and SiO2 in the visible to near-infrared bands are extracted by measuring with a spectroscopic ellipsometry and fitting with a dispersion model. The data are then imported into the material library of the optical thin film design software. Step S2: Create an air / (TiN / SiO2) structure in the optical thin film design software. n / A multilayer film structure model for a transparent substrate, wherein the thickness of a single TiN film is not less than 2nm and the thickness of a single SiO2 film is not less than 10nm; Step S3: Perform inverse global optimization on the multilayer film structure model, assuming discrete sampling points in the 400-800nm ​​visible light wavelength range are... ( i =1,2,…,m), the multilayer film structure model includes the number of periods n and the thicknesses of each TiN sublayer and SiO2 sublayer as adjustable design variables. The theoretical reflectance at each sampling point is ;in The calculations, based on the transfer matrix method and performed by optical thin film design software, specifically involve multilayer film structures at wavelengths... Input admittance at the location It is obtained recursively from the characteristic matrix of the membrane system; Define average reflectance: ; in: — Number of wavelength sampling points; — The reflectivity at the i-th sampling wavelength is calculated based on the transfer matrix method; —The complex refractive index of the incident medium, where the incident medium is air, take = 1.0 + 0i; — Multilayer film structures at wavelength Input admittance at the location; The peak reflectivity constraint is set as follows: ; Define the overall objective function as a weighted penalty function for the constraints of average reflectance and peak reflectance: in =100 is the penalty factor. When the peak reflectivity exceeds the 0.5% threshold, a large penalty term is applied to ensure that the optimization prioritizes meeting the peak constraint. By making the weighted penalty function Minimize the thickness to obtain the design thickness of each sublayer; Step S4: Based on the designed thickness of each sublayer output in Step S3, TiN thin films and SiO2 thin films are alternately deposited from bottom to top on the target transparent substrate using plasma-enhanced atomic layer deposition technology to form a (TiN / SiO2) layer with SiO2 layer as the top layer. n Nanostructured stacked structure; Step S5: Measure the absolute reflectance spectrum of the sample obtained in step S4 in the 400-700nm wavelength range; Step S6: Perform reverse fitting between the measured absolute reflectance spectrum and the theoretical simulation spectrum in step S3, and correct the thickness of each sublayer or recalibrate the optical constants of the material based on the fitting deviation; Step S7: Repeat steps S4 to S6 until the measured average reflectance is less than 0.2% and the peak reflectance is less than 0.5%, thus obtaining the TiN / SiO2 nanolayered ultra-low reflectance film.

2. The method for preparing a TiN / SiO2 nanolayered ultra-low reflectance film according to claim 1, characterized in that, In step S1: When depositing TiN thin film, TiCl4 is used as titanium precursor and NH3 plasma is used as nitrogen source, and the deposition temperature is 80℃-120℃; when depositing SiO2 thin film, bis(diethylamino)silane is used as silicon precursor and O2 plasma is used as oxygen source, and the deposition temperature is 80℃-120℃. The ellipsometric spectrum of the TiN thin film was fitted using the Tauc-Lorentz oscillator model, and the ellipsometric spectrum of the SiO2 thin film was fitted using the Cauchy dispersion model. The refractive index and extinction coefficient at each wavelength were obtained by inversion.

3. The method for preparing a TiN / SiO2 nanolayered ultra-low reflectance film according to claim 1, characterized in that, (TiN / SiO2) in step S2 n In this context, n ranges from 1 to 6.

4. The method for preparing a TiN / SiO2 nanolayered ultra-low reflectance film according to claim 1, characterized in that, In step S3, the reverse global optimization iterates through the layers one by one with n as a discrete variable. For each value of n, the initial thickness of each TiN sublayer is set to 10 nm, and the initial thickness of each SiO2 sublayer is set to 30 nm. This global optimization is then performed on the thickness of each sublayer to optimize the weighted penalty function. minimize.

5. The method for preparing a TiN / SiO2 nanolayered ultra-low reflectance film according to claim 1, characterized in that, Before step S4, a substrate pretreatment step is included: the target transparent substrate is ultrasonically cleaned in acetone, isopropanol, and deionized water in sequence, dried with high-purity nitrogen, and then sent into the plasma-enhanced atomic layer deposition reaction chamber, where a vacuum is drawn until the background vacuum level is lower than 3 × 10⁻⁶. -2 Torr, then heat the substrate to 100°C and hold it at that temperature until thermal equilibrium is reached.

6. The method for preparing a TiN / SiO2 nanolayered ultra-low reflectance film according to claim 1, characterized in that, In step S5, an ultraviolet-visible-near-infrared spectrophotometer is used to measure the measured absolute reflectance spectrum under near-normal incidence conditions.

7. The method for preparing a TiN / SiO2 nanolayered ultra-low reflectance film according to claim 1, characterized in that, The constraints for the inverse fitting in step S6 are: the optical constants of TiN are adjusted within ±5% of the calibration value, the refractive index of SiO2 is adjusted within ±1% of the calibration value and the extinction coefficient is fixed at zero, and the thickness of each sublayer is adjusted within ±15% of the design value; when the fitting objective function decreases by less than one part per million for 5 consecutive iterations, or the goodness of fit R... 2 The fitting process stops when the value is greater than 0.999 or when the upper limit of 10,000 iterations is reached.

8. The method for preparing a TiN / SiO2 nanolayered ultra-low reflectance film according to claim 1, characterized in that, The specific method for correcting the thickness of each sublayer or recalibrating the optical constants of the material in step S6 is as follows: when the measured average reflectivity is between 0.2% and 0.3% and the measured peak reflectivity is between 0.5% and 0.7%, the number of atomic layer deposition cycles is adjusted proportionally to the ratio of the fitted actual thickness to the designed thickness; when the measured average reflectivity is ≥ If the deviation of the material optical constant from the calibration value exceeds 5% by 0.3%, the material optical constant is recalibrated and steps S2 to S3 are repeated to optimize the structural design; if the standard is still not met after three consecutive rounds of correction, the equipment is inspected.

9. A TiN / SiO2 nanolayered ultra-low reflectance film, characterized in that, It is prepared by the preparation method described in any one of claims 1-8.

10. The TiN / SiO2 nanolayered ultra-low reflectance film according to claim 9, characterized in that, In the 400-700nm visible light band, the average reflectivity of the TiN / SiO2 nanolayer ultra-low reflectivity film is less than 0.2%, and the peak reflectivity is less than 0.5%.